Quantitative detection method for thickness of fatigue damage layer of bearing inner ring on supporting roller

Through X-ray diffraction and electrolytic polishing technology, the residual stress and half-height width changes of the inner ring of the bearing roller are analyzed, and the thickness of the fatigue damage layer is accurately evaluated, which solves the problem of large errors in the existing technology, and improves the accuracy of detection and Reliability of repair.

CN119310118APending Publication Date: 2025-01-14BAOSHAN IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310852776.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art lacks an accurate quantitative evaluation method for fatigue damage of the inner ring of the bearing roller bearing, resulting in large errors, affecting repair decision-making and resource utilization efficiency.

Method used

X-ray diffraction method is used to measure the residual stress and half-height width changes on the surface of the bearing inner ring. Combined with electrolytic polishing technology, the change rate of half-height width is analyzed along the depth direction to determine the thickness of the fatigue damage layer.

Benefits of technology

Accurate detection of the thickness of the fatigue damage layer in the inner ring of the bearing roller is achieved, reducing errors, improving the reliability of repair decisions and resource utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310118A_ABST
    Figure CN119310118A_ABST
Patent Text Reader

Abstract

The invention discloses a method for quantitatively detecting the thickness of a fatigue damage layer of a bearing inner ring on a supporting roller, which comprises the following steps of: measuring and analyzing the surface residual stress of the bearing inner ring and the change of the full width at half maximum by adopting an X-ray diffraction method, determining a fatigue area, and determining the thickness of the fatigue damage layer through the change of the full width at half maximum along the thickness direction by utilizing an electrolytic polishing mode. The method overcomes the defects existing in a traditional method for evaluating the thickness of the contact fatigue damage layer of the inner ring through hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a contact fatigue damage detection technology for inner ring parts of support roller bearings of a steel metallurgical rolling mill, and more specifically to a quantitative detection method for the thickness of a fatigue damage layer of an inner ring of a support roller bearing. Background Art

[0002] The inner ring of the support roller bearing is a key component on the steel rolling production line. During the use of the machine, the outer surface of the inner ring of the support roller bearing contacts the cylindrical roller, resulting in rolling contact fatigue, fatigue hardening on the surface, and defects such as wear, meat loss or pitting. The fatigue layer affects the service life of the inner ring. When fatigue peeling occurs on the surface of the inner ring of the bearing, a new inner ring must be replaced. At present, after the cold rolling support roller is removed from the machine each time the bearing seat is removed, only the inner ring of the bearing is visually inspected. The outer surface of the inner ring of the bearing is not repaired during the service of the support roller. If the outer surface of the inner ring of the bearing peels off, a new inner ring is replaced. If there is no abnormality on the outer surface of the inner ring of the bearing, the support roller is scrapped. However, during the use of the support roller, the inner ring of the bearing of some support rollers is scrapped due to peeling of the roller body, the hardness of the roller body drops to the scrap hardness, or the use is to the scrap size. The damage to the inner ring of the support roller is relatively small and still has good performance. After being repaired by appropriate repair technology, it can be used for other support rollers whose inner rings need to be replaced, and continue to be used until the support roller is scrapped, reducing the production cost and resource waste of the steel mill. However, the hardness measurement method is currently the main method used, which has large errors. In the absence of a more accurate quantitative assessment technology for fatigue damage of the inner ring of the backup roller bearing, some inner rings are not dared to be used after grinding.

[0003] X-ray diffraction technology is a commonly used non-destructive material testing technology. The half-width of the diffraction peak of polycrystalline materials is closely related to the microstructural changes of the materials. The organizational structure of the material, such as crystal block size, microscopic distortion, dislocation density, etc., is the main factor causing the broadening of the physical line shape. Under the action of external loads, the material will cause the surface structure to be refined, the microscopic distortion increases, the dislocation density increases, and other organizational changes, which will eventually lead to the broadening of the X-ray diffraction line shape. Yang Rongsong et al. published a paper entitled “Effect of Residual Stress and Its Characterization Parameters on Rolling Contact Performance of Materials” in Journal of Sichuan University (Engineering Science Edition) Vol. 48, No. 4 (2016), which deeply studied the influence of residual stress on rolling contact. Residual compressive stress can reduce the contact stress in the elastic deformation stage and the plastic strain in the plastic deformation stage. Mario Guagliano et al. published “Contact fatigue damage analysis of shot peened gears by means of X-ray measurements” in Engineering Failure Analysis 16 (2009) 964–971, which analyzed the changes in residual stress and half-height width of shot peened gears at different stages of use. The results showed that the residual compressive stress formed by shot peening would relax to a certain extent, and the half-height width would also decrease to a certain extent.

[0004] Therefore, according to the existing literature, the formation and evolution of the damage layer during contact fatigue are closely related to the changes in residual stress and half-width. The fatigue damage area is determined by comparing the surface residual stress and half-width. The thickness of the fatigue damage layer can be determined by comparing the half-width distribution of the fatigue zone and the original zone along the depth direction. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the bearing on the support roller, so as to overcome the defects of the traditional method of evaluating the thickness of the inner ring contact fatigue damage layer by hardness.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A quantitative detection method for the thickness of the fatigue damage layer of the inner ring of the bearing on the support roller:

[0008] The X-ray diffraction method is used to measure and analyze the residual stress on the surface of the inner ring of the bearing and the change of the half-height width to determine the fatigue zone. The electrolytic polishing method is used to determine the thickness of the fatigue damage layer through the change of the half-height width along the thickness direction.

[0009] Preferably, the method of measuring and analyzing the residual stress and half-width at half maximum on the surface of the inner ring of the bearing by using an X-ray diffraction method to determine the fatigue zone specifically includes the following steps:

[0010] (1) Determine the material of the inner ring of the bearing, select an X-ray target according to the material structure type, and design the test position distribution on the surface of the inner ring of the bearing;

[0011] (2) Using an X-ray stress meter to obtain the residual stress and half-width at different positions on the surface of the inner ring of the bearing, comparing the distribution of the residual stress and half-width, and determining the fatigue zone and the non-fatigue zone.

[0012] Preferably, in step (1), a plurality of test positions are arranged at equal intervals along the axial direction of the inner ring of the bearing; and

[0013] The diffraction peak of the crystal plane diffraction angle is selected as the measurement peak of residual stress.

[0014] Preferably, in step (2), the residual stress in the fatigue zone is 50% greater than the residual stress in the non-fatigue zone, and the half-width at half-maximum of the fatigue zone is 10% greater than the half-width at half-maximum of the non-fatigue zone.

[0015] Preferably, the test positions are spaced equidistantly along the axial direction of the bearing inner ring and are between 1 and 5 cm.

[0016] Preferably, the crystal plane diffraction angle is greater than 120°.

[0017] Preferably, the method of determining the thickness of the fatigue damage layer by the change of the half-height width along the thickness direction by electrolytic polishing specifically comprises the following steps:

[0018] (3) selecting the test position in the fatigue zone, then selecting the corrosion peeling area, performing peeling treatment by electrolytic polishing, determining the peeling thickness, and measuring the half-height width result of the thickness position by using an X-ray stress analyzer;

[0019] (4) Repeat step (3) to obtain the half-width values ​​at different depths, and draw a depth-half-width curve. When the change rate of the half-width values ​​of the fatigue zone and the non-fatigue zone is continuously less than a set value, the corresponding thickness is the fatigue damage thickness.

[0020] Preferably, in step (3), 1 to 3 test positions are selected;

[0021] The size of the corrosion and peeling area is between 1 cm×1 cm and 5 cm×5 cm.

[0022] Preferably, the electrolytic polishing method in step (3) uses saturated salt water as the solution, the DC voltage is between 1 and 15V, and the current is between 1 and 5A.

[0023] Preferably, the set value in step (4) is 5%.

[0024] The present invention provides a quantitative detection method for the thickness of the fatigue damage layer of the inner ring of the bearing on a support roller. The fatigue zone and the original zone are determined by measuring the changes in the residual stress and half-width at half height on the surface of the inner ring of the support roller bearing. The half-width at half height of the fatigue zone and the original zone are tested along the depth direction, and a half-width at half height-depth curve is drawn. The thickness of the damage layer is determined by analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the process of the quantitative detection method of fatigue damage layer thickness of the present invention;

[0026] Figure 2 Schematic diagram of the test position of the inner ring of the bearing on the support roller in Example 1 of the method for quantitatively detecting the thickness of the fatigue damage layer of the present invention;

[0027] Figure 3 Schematic diagram of residual stress and half-width distribution in the inner ring surface test area in Example 1 of the method for quantitatively detecting the thickness of fatigue damage layer of the present invention, (a) is residual stress, (b) is half-width;

[0028] Figure 4 Schematic diagram of the distribution pattern of the half-width at half maximum of the inner race fatigue zone and the original zone with layer depth in Example 1 of the method for quantitatively detecting the thickness of the fatigue damage layer of the present invention. DETAILED DESCRIPTION

[0029] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0030] Combination Figure 1 As shown, the present invention provides a method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the bearing on the support roller:

[0031] The X-ray diffraction method is used to measure and analyze the residual stress on the inner ring surface of the bearing and the change of the half-height width to determine the fatigue zone, and the thickness of the fatigue damage layer is determined by the change of the half-height width along the thickness direction using electrolytic polishing. The specific steps include:

[0032] (1) Determine the material of the bearing inner ring, select the X-ray target according to the material structure type, and design the test position distribution on the bearing inner ring surface;

[0033] Determine the material phase and select the diffraction peak with a suitable high diffraction angle (the crystal plane diffraction angle is greater than 120°) as the residual stress measurement peak.

[0034] For ferrite, martensite and carburizing steel, Cr targets are used, the diffraction crystal plane is (211), and the material surface does not need any treatment. The test positions are equally spaced along the axial direction of the bearing inner ring and are between 1 and 5 cm.

[0035] (2) Use an X-ray stress meter to obtain the residual stress and half-width at different locations on the inner ring surface of the bearing, compare the distribution of residual stress and half-width, and determine the fatigue area and non-fatigue area;

[0036] The residual stress and half-width of the fatigue zone change to a certain extent relative to the non-fatigue zone (original zone), and the width of the fatigue zone is determined based on the change, that is, the residual stress in the fatigue zone is 50% greater than the residual stress in the non-fatigue zone, and the half-width of the fatigue zone is 10% greater than the half-width of the non-fatigue zone.

[0037] (3) Select 1 to 3 test positions in the fatigue zone, and then select the corrosion stripping area, and use electrolytic polishing to perform local corrosion stripping treatment. The area is between 1 cm×1 cm and 5 cm×5 cm, the DC voltage is between 1 and 15 V, and the current is between 1 and 5 A. By controlling the time, the stripping thickness is determined, and the half-height width result of the thickness position is measured using an X-ray stress analyzer (it is necessary to ensure that the size of the collimator used is smaller than the area of ​​the corrosion stripping area);

[0038] The electrolytic polishing method uses saturated salt water as the solution.

[0039] (4) Repeat step (3) to obtain the half-width at different depths and draw a depth-half-width curve. When the change rate of the half-width at 2 or 3 consecutive points in the fatigue zone and the non-fatigue zone is less than the set value (5%), it can be considered that it is basically stable after that point, and the corresponding thickness is the fatigue damage thickness.

[0040] Example

[0041] This embodiment provides a method for quantitatively detecting the thickness of a fatigue damage layer of an inner ring of a bearing on a support roller, which specifically includes the following steps:

[0042] (1) Select the inner ring sample of the bearing of the support roller, determine that its material is carburized and tempered martensite, and select an area with a width of about 30 cm on its surface as the test area (such as Figure 2 As shown in the figure, test positions are set in the middle along the axial direction at equal intervals of 2 cm, with a total of 20 test positions.

[0043] (2) X-ray diffraction test was performed on the test position using an X-ray stress analyzer. The specific parameters of the X-ray stress analyzer in the test were voltage 25 kV, tube current 30 mA, Cr target Kα radiation, and radiation area 1×2 mm 2, select (211) diffraction crystal plane, 512-channel position-sensitive detector, 2θ range 29°, ψ angle optimized within ±35° 17 stations, co-inclined diffraction geometry, ψ swing angle 2° at each station, X-ray elastic constant S 2 / 2=6.50×10 -6 MPa -1 and S 1 =-1.56×10 -6 MPa -1 . Where θ and ψ refer to the X-ray diffraction angle of the material and the azimuth angle of the residual stress test respectively. The surface residual stress and half-height width test results are as follows Figure 3 As shown in the figure, since some areas of the bearing of the support roller are not in contact during use and are in the original state, there are differences in the residual stress and half-width between the contact fatigue zone and the original zone. The analysis results show that the area with large residual compressive stress and small half-width is the fatigue zone for the inner ring sample, and the area with small residual stress and large half-width is the original zone. The width of the fatigue zone and the original zone can be preliminarily determined.

[0044] (3) Select one point in the original area and one point on the left and right of the fatigue area to set up a 2×2 cm area, and perform electrochemical polishing on the area. The voltage is 10 V and the current is 3 A. The electrochemical corrosion stripping rate is 1 micron / second through testing. The time is set to 5s, 15s, 25s, 50s, 75s, 100s, 150s, and 300s (all times are cumulative time). After each stripping treatment, the half-height width is measured using an X-ray stress meter.

[0045] (4) The half-width-depth distribution curves of the fatigue zone and the non-fatigue zone are drawn, and the thickness of the contact fatigue damage layer is determined to be 100 μm by comparison.

[0046] The measurement results show that the fatigue zone and the original state area can be determined by measuring the residual stress and half-width change of the inner ring surface of the support roller using the X-ray diffraction method. The thickness of the contact fatigue damage layer can be evaluated by comparing and analyzing the distribution of the half-width of the inner ring fatigue zone and the original state zone with the layer depth. The method has a clear theory and can directly evaluate the thickness of the fatigue damage layer by testing the residual stress and half-width of the inner ring of the support roller.

[0047] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the bearing on the support roller, characterized in that: The X-ray diffraction method is used to measure and analyze the residual stress on the surface of the inner ring of the bearing and the change of the half-height width to determine the fatigue zone. The electrolytic polishing method is used to determine the thickness of the fatigue damage layer through the change of the half-height width along the thickness direction.

2. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 1, characterized in that: The X-ray diffraction method is used to measure and analyze the residual stress on the surface of the inner ring of the bearing and the change of the half-height width to determine the fatigue zone, which specifically includes the following steps: (1) Determine the material of the inner ring of the bearing, select an X-ray target according to the material structure type, and design the test position distribution on the surface of the inner ring of the bearing; (2) Using an X-ray stress meter to obtain the residual stress and half-width at different positions on the surface of the inner ring of the bearing, comparing the distribution of the residual stress and half-width, and determining the fatigue zone and the non-fatigue zone.

3. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 2 is characterized in that: In step (1), a plurality of test positions are arranged at equal intervals along the axial direction of the inner ring of the bearing; and The diffraction peak of the crystal plane diffraction angle is selected as the measurement peak of residual stress.

4. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller upper bearing according to claim 3 is characterized in that: In the step (2), the residual stress in the fatigue zone is 50% greater than the residual stress in the non-fatigue zone, and the half-width at half-maximum of the fatigue zone is 10% greater than the half-width at half-maximum of the non-fatigue zone.

5. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 4 is characterized in that: The test positions are spaced evenly along the axial direction of the bearing inner ring and are between 1 and 5 cm.

6. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller upper bearing according to claim 4, characterized in that: The diffraction angle of the crystal plane is greater than 120°.

7. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 4, characterized in that: Determining the thickness of the fatigue damage layer by the change of the half-height width along the thickness direction by electrolytic polishing specifically comprises the following steps: (3) selecting the test position in the fatigue zone, then selecting the corrosion peeling area, performing peeling treatment by electrolytic polishing, determining the peeling thickness, and measuring the half-height width result of the thickness position by using an X-ray stress analyzer; (4) Repeat step (3) to obtain the half-width values ​​at different depths, and draw a depth-half-width curve. When the change rate of the half-width values ​​of the fatigue zone and the non-fatigue zone is continuously less than a set value, the corresponding thickness is the fatigue damage thickness.

8. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 7, characterized in that: Selecting 1 to 3 of the test positions in step (3); The size of the corrosion and peeling area is between 1 cm×1 cm and 5 cm×5 cm.

9. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 7, characterized in that: The electrolytic polishing method in step (3) uses saturated salt water as a solution, the DC voltage is between 1 and 15V, and the current is between 1 and 5A.

10. The method for quantitatively detecting the thickness of the fatigue damage layer of the inner ring of the support roller bearing according to claim 7, characterized in that: The set value in step (4) is 5%.